A competição das empresas na era do conhecimento e alguns dos possíveis desdobramentos das interações políticas, econômicas e sociais: uma reflexão - Martins, Erasmo Flavio Moreno (2004)
This text is a reflection about the environment in which the capitalist organizations compete nowadays and also about some economic policies that contribute to the process of changes in the organizations and ways of management. It considers the phenomenon that take the knowledge as a direct factor of production, its criative processes and the need of its management. Some questions considered important for the dynamics of this new stage of capitalist accumulation in which are briefly taken into account the financial globalization that subordinates the productive new arrengements. The Washington Consensus, the rules for intelectual property and the patent recognition are integrant parts of these subjects. From the scientific point of view, the implications of the nonlinear dynamics (Chaos Theory) in the economy and in the management complete the conceptual structure ofthis dissertation.